A Sociodemographic Review of Household Food Management Learning to Reduce Food Waste in Coastal Areas - Abdul Rasid Syukri; Maswadi Maswadi; Wanti Fitrianti (Civiliza Publishing, Indonesia., 2025)
Food loss and waste have become a critical global concern, particularly in the context of ongoing hunger issues worldwide. It is estimated that nearly one-third of all food produced for human consumption is ultimately discarded. In Indonesia, food waste occurs across multiple sectors, with households contributing the largest share approximately 63.64%, or around 77 kg per capita annually. Sambas Regency, a coastal area in West Kalimantan, is also confronted with challenges related to waste disposal behavior and management systems. In Paloh District, the volume of waste entering coastal areas reaches approximately 963.60 tons per year, indicating a significant level. This study is essential as it seeks to examine socio-demographic characteristics and household behaviors related to food waste among coastal communities in Sambas Regency. Data were collected through surveys and structured questionnaire interviews involving 100 respondents in Paloh District. The analysis employed the Spearman rank correlation method. The findings reveal that socio-demographic variables such as education level, income, expenditure, and household size are associated with food waste behavior. Key drivers of food waste include excessive cooking practices, inadequate storage methods, poor meal planning, inaccurate estimation of food needs, and cultural practices during certain events that encourage food disposal behavior.